In the path of the moon : Babylonian celestial divination and its legacy - Rochberg, Francesca, 1952- (Ancient Magic and Divination, 2010)
Celestial divination, in the form of omens from lunar, planetary, astral, and meteorological phenomena, was central to Mesopotamian cuneiform scholarship and science from the late second millennium BCE into the Hellenistic period. Beyond the boundaries of ancient Mesopotamia, the ideas, texts, and traditions of Babylonian celestial divination are traceable in Hellenistic sciences and philosophies. This collection of essays investigates features of Babylonian celestial divination with special focus on those aspects that influenced later Greco-Roman astronomy, astrology, and theories of signs. A multi-faceted collection of philological, historical, and philosophical investigations, In the Path of the Moon offers Assyriologists, Classicists, and historians of ancient science a wide-ranging series of studies unified around the theme of Babylonian celestial divination's legacy. \'The collected essays in this volume, successive steps in an ordered path, constitute an invaluable contribution to a better understanding of Babylonian divination.\' Lorenzo Verderame, \'Sapienza\' Università di Roma \'The reader interested in the multifaceted presentation of the problems related to the explanation of Babylonian celestial divination and well equipped with the knowledge of Akkadian will certainly be rewarded by the study of Rochberg's latest publication.\' Henryk Drawnel, SDB